STRATEGI PENDIDIKAN KONTEMPORER DALAM MENGEMBANGKAN KOGNITIF ANAK USIA DINI: SYSTEMATIC LITERATURE REVIEW - Elya Nora; Farida Mayar; Humairah; Windi Elsa Putri; Wiwit April Mardiyanti; Zahra Tsabita Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to identify and analyze contemporary educational strategies that are effective in developing cognitive abilities in early childhood through a Systematic Literature Review (SLR) approach. The SLR method was carried out by selecting articles published between 2015 and 2025 from various databases from Google Scholar, Scopus, ScienceDirect, and SpringerLink. using the keywords "Strategy, Cognitive, Contemporary Education, and early childhood". Of the total articles found, a number of studies met the inclusion criteria based on methodological quality and theme relevance. The results of the analysis showed that the most dominant and effective contemporary educational strategies include project-based learning, technology-integrated play, STEM approaches for early childhood, classroom-based social-emotional learning, and collaborative learning models. These strategies have been shown to improve cognitive aspects such as problem-solving skills, creativity, critical thinking, memory, and language development. This study concludes that implementing contemporary educational strategies oriented toward real-life experiences, collaboration, and the use of technology can significantly strengthen early childhood cognitive development. Recommendations focus on developing an early childhood education curriculum that adapts to learning innovations and improving educator competency to effectively integrate contemporary strategies in the classroom.